2016
DOI: 10.1016/j.ebiom.2016.10.025
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Human Tribbles Homolog 3 Genetic Variation (rs2295490) Effects on Type 2 Diabetes Patients with Glucose Control and Blood Pressure Lowering Treatment

Abstract: Effects of human tribbles homolog 3 (TRIB3) genetic variation (c.251 A > G, Gln84Arg, rs2295490) on the clinical outcomes of vascular events has not been evaluated in patients with type 2 diabetes after blood pressure lowering and glucose controlling treatment. We did an analysis of a 2 × 2 factorial (glucose control axis and blood pressure lowering axis) randomized controlled clinical trial at 61 centers in China, with a follow-up period of 5 years. The major vascular endpoints were the composites of death fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We performed a retrospective pharmacogenomic analysis using samples and data from a 2 × 2 factorial randomized controlled trial conducted in 61 centers in China over a follow-up period of 5 years. The original study protocol and details have been published previously (Patel et al, 2007; Group et al, 2008; He et al, 2016). Briefly, approval to conduct the trial was obtained from the ethics committee of each study center, and informed consent was obtained from all subjects (registration number NCT00145925).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a retrospective pharmacogenomic analysis using samples and data from a 2 × 2 factorial randomized controlled trial conducted in 61 centers in China over a follow-up period of 5 years. The original study protocol and details have been published previously (Patel et al, 2007; Group et al, 2008; He et al, 2016). Briefly, approval to conduct the trial was obtained from the ethics committee of each study center, and informed consent was obtained from all subjects (registration number NCT00145925).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, patients with AG or GG genotypes experienced significantly fewer primary vascular events after receiving intensive glucose control treatment [aiming for a hemoglobin (Hb) A1c value of 6.5% or lower] as compared with patients receiving standard glucose treatment (patients who continued with their usual glucose control regimens). However, such a benefit was not observed in patients with the AA genotype (He et al, 2016). T2DM is a disease with complex traits, and a previous study suggested that core disease-related genes and genes outside of core pathways are sufficiently interconnected to affect its heritability (Boyle et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…A recent study identified that TRIB3 was up-regulated in NSCLC that promoted the metastasis and tumor growth [ 17 ]. Furthermore, TRIB3 has a pivotal role in insulin signaling transduction pathway [ 18 ], and the DM-induced tumor progression [ 19 ]. Thus, it is reasonable to infer that TRIB3 may participate in the development of NSCLC induced by HG.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that TRIB3 has an integral role in regulating the blood pressure, and its genetic variation (251, A > G) may cause a variability of antihypertensive drug therapy. Our previous findings have suggested a greater benefit on vascular outcomes in patients carrying TRIB3 (rs2295490) G allele with good glucose and blood pressure control (He et al, 2016). TRIB3 (rs2295490) AG/GG genotypes were found to reduce primary vascular events in patients who received intensive glucose treatment as compared to those receiving standard glucose treatment in type 2 diabetic patients (He et al, 2018).…”
Section: Introductionmentioning
confidence: 99%